Commitment to organizations and occupations: Extension and test of a three-component conceptualization. - Meyer, John P.; Allen, Natalie J.; Smith, Catherine A. (Journal of Applied Psychology, 1993)
he authors tested the generalizability of J. P. Meyer and N. J. Allen's (1991) 3-component model of organizational commitment to the domain of occupational commitment. Measures of affective, continuance, and normative commitment to occupation were developed and used to test hypotheses concerning their differential relations with antecedent and consequence variables. Confirmatory factor analyses conducted on data collected from samples of student and registered nurses revealed that the 3 component measures of occupational commitment were distinguishable from one another and from measures of the 3 components of organizational commitment